Development of ABM for the subject of design and technology in practical session of constructing aquaponics system design module - Hassan, M. H.; Kob, C. G. C.; Ghani, N. L. C.; Khairudin, M. (AIP conference proceedings, 2023)
This study was conducted to assist teachers and students in teaching and learning during the subtopic practical sessions of constructing aquaponics system design. A total respondent of 5 teachers and 30 students were involved in this study. This study aims to improve students’ mastery of understanding on the topic of building aquaponics system design models and facilitate teachers to plan lessons. The study was conducted in the form of a teaching aid called an aquaponics model teaching box. Researchers have used the questionnaire method to obtain the total data collected. The results of the questionnaire and video teaching aids showed that the aquaponics model teaching box successfully helps teachers and students in teaching and learning. Students showed a positive response and teachers accepted the suggestions of teaching aids developed. Based on the questionnaire as well, students were more interested in this aquaponics model teaching box.